2020
DOI: 10.3390/su12187422
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Pervious Pavements through Nomenclature, Standards, and Holistic Green Design

Abstract: Researchers developing pervious pavements over the past few decades have commendably demonstrated long-term run-off reduction using a diverse collection of materials. Today, pervious pavements are widely recognized as a low impact development technique and a type of green infrastructure, and installations are proliferating throughout the United States and worldwide. The entire field of pervious pavements though, is being profoundly stunted by three persistent problems: conflicting nomenclature, flawed testing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Chai et al [4] analyzed how freeze-thaw cycles affect the durability of permeable pavements and discovered an air void high limit of 21% for porous asphalt in freezing regions. Quite different was the approach adopted by Sprouse III et al [5] They proposed changes in the nomenclature and standards for pervious pavements and developed a ten-part holistic green design framework for these types of pavements, which should drastically improve their durability.…”
Section: Contents Of the Special Issuementioning
confidence: 99%
“…Chai et al [4] analyzed how freeze-thaw cycles affect the durability of permeable pavements and discovered an air void high limit of 21% for porous asphalt in freezing regions. Quite different was the approach adopted by Sprouse III et al [5] They proposed changes in the nomenclature and standards for pervious pavements and developed a ten-part holistic green design framework for these types of pavements, which should drastically improve their durability.…”
Section: Contents Of the Special Issuementioning
confidence: 99%
“…Unlike regular concrete modified in various ways [ 5 ], an open porous structure makes pervious concrete a particular type that allows water to flow freely through its structure. Pervious concrete has been successfully used for years in road and pedestrian water-permeable solutions in the U.S., Japan, Canada, and many European countries [ 6 ]—pervious concrete pavements allow quick and effective drainage of rainwater to the ground or an additional rainwater recovery system and enable cleaning and cooling of water during its flow through successive pavement layers. According to research [ 7 ], a square meter of porous concrete pavement can drain from 80 to 730 L of water per minute, which allows for a significant reduce the phenomenon of surface runoff, even in the case of heavy rainfall, while being able to remove up to 90% of total suspended solids [ 8 ] and heavy metals [ 9 ] from stormwater runoff, making it safe for discharge into water reservoirs or the surrounding ground without the need of further treatment.…”
Section: Introductionmentioning
confidence: 99%
“…They also reported that without adjusting the mix design, geopolymer mixtures improve the permeability but indirectly decrease the tensile strength of PCP. Recently, Sprouse III et al [23] examined three continuing problems in PCP applications, including conflicting nomenclature, flawed testing standards, and the absence of an inclusive design framework.…”
Section: Introductionmentioning
confidence: 99%